2019
DOI: 10.1177/0310057x19838753
|View full text |Cite
|
Sign up to set email alerts
|

Conservative versus conventional oxygen therapy for cardiac surgical patients: A before-and-after study

Abstract: Avoiding hypoxaemia is considered crucial in cardiac surgery patients admitted to the intensive care unit (ICU). However, avoiding hyperoxaemia may also be important. A conservative approach to oxygen therapy may reduce exposure to hyperoxaemia without increasing the risk of hypoxaemia. Using a before-and-after design, we evaluated the introduction of conservative oxygen therapy (target SpO2 88%–92% using the lowest FiO2) for cardiac surgical patients admitted to the ICU. We studied 9041 arterial blood gas (AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…To date, no RCT comparing liberal (conventional) and conservative oxygen therapy has focused on postoperative patients. To our knowledge, only one study, uncontrolled before-and-after design, has evaluated the introduction of conservative oxygen therapy (target SpO 2 of 88–92%) for cardiac surgical patients admitted to the intensive care unit [ 53 ]. Accordingly, this study found that conservative oxygen therapy could promote a significant decrease in hyperoxemia exposure without increasing the incidence of severe hypoxemia.…”
Section: Re-evaluation Of Postoperative Oxygen Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…To date, no RCT comparing liberal (conventional) and conservative oxygen therapy has focused on postoperative patients. To our knowledge, only one study, uncontrolled before-and-after design, has evaluated the introduction of conservative oxygen therapy (target SpO 2 of 88–92%) for cardiac surgical patients admitted to the intensive care unit [ 53 ]. Accordingly, this study found that conservative oxygen therapy could promote a significant decrease in hyperoxemia exposure without increasing the incidence of severe hypoxemia.…”
Section: Re-evaluation Of Postoperative Oxygen Therapymentioning
confidence: 99%
“…Although such findings might support the feasibility and physiological safety of conservative oxygen therapy in patients admitted to the intensive care unit after surgery, currently available studies do not provide sufficient evidence to guide practice regarding postoperative oxygen therapy. In addition, there might be a discrepancy in oxygen levels defined as liberal oxygen therapy between the clinical studies comparing two different oxygen targets [ 51 53 ] and in the levels reported to exert physiological harmful effects of supplemental oxygen and hyperoxemia [ 18 , 21 , 22 ]. So far, no clinical studies have examined the threshold for the onset of the association of hyperoxemia or hypoxemia with poor outcomes in patients postoperatively.…”
Section: Re-evaluation Of Postoperative Oxygen Therapymentioning
confidence: 99%
“…Conventional therapy would put 44.5% of the patients exposed to hyperoxemia, which is only about 11.4% in conservative oxygen group. 20 The disadvantages of hyperoxemia have been well demonstrated by many researches. First of all, high inspired oxygen concentrations would inhibit immune system: compromising the ability of macrophages, 23 suppressing the production of cytokine, 24 causing structural changes within alveolar macrophages and leading to serious impairment of their antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…16,17,19−22 Three studies were randomized controlled trials (RCTs), 16,17,21 1 studies was retrospective nest cohort analysis, 19 and the other 2 studies was prospective before-after study. 20,22 Mortality was reported in 6 studies, among which hospital mortality and ICU mortality was reported in 3 studies, 16,19,20 28 day mortality was reported in 2 studies, 19,22 , 30 day mortality was reported in 1 study, 20 90 day mortality was reported in 2 studies, 17,21 180 day mortality was reported in 1 study. 17 ICU LOS was presented in 5 studies, 16,17,19−21 Hospital LOS was reported in 5 studies.…”
Section: Study Descriptionmentioning
confidence: 99%
See 1 more Smart Citation